Development and characterization of new nickel coatings for application in alkaline water electrolysis. (5th January 2016) - Kuleshov, V.N.; Kuleshov, N.V.; Grigoriev, S.A.; Udris, E.Y.; Millet, P.; Grigoriev, A.S.
Abstract: The purpose of this paper is to report on the synthesis and characterization of different electrocatalytic materials for the hydrogen and oxygen evolution reactions (HER and OER) in alkaline water electrolysis. Ni meshes surface coated with porous nickel layers have been used as substrates for electrodes. Porous nickel coatings have been modified by amorphous NiPx or Pt nanoparticles (to improve the cathode efficiency) and nickel–cobalt spinels (to improve the anode efficiency). The structure, roughness and composition of the active layers have been determined by SEM analysis, porosimetry, laser atomic emission spectroscopy (LAES), energy-dispersion analysis (EDA) and XRD analysis. Overpotentials for both HER and OER have been measured in 6 M KOH over the 0–1.0 A/cm 2 current density range. Both hydrogen and oxygen overpotentials are found significantly reduced compared to smooth nickel electrodes. The hydrogen and oxygen evolution mechanisms on these catalytic surfaces are discussed. Highlights: New nickel coatings with high porous structures have been developed. Synthesis of porous coating significantly simplifies spinel-like catalysts formation. Obtained electrocatalytic materials used for hydrogen and oxygen evolution reactions.